Cyclo-oxygenase-2 (COX-2) expression at the site of recent myocardial infarction: friend or foe?. Issue 4 (12th March 2004) - Abbate, A; Santini, D; Biondi-Zoccai, G G L; Scarpa, S; Vasaturo, F; Liuzzo, G; Bussani, R; Silvestri, F; Baldi, F; Crea, F; Biasucci, L M; Baldi, A
Abstract : Background: Cyclo-oxygenase-2 (COX-2) is induced in cardiomyocytes only in response to stress, such as ischaemia. Objective: To assess COX-2 expression at the site of recent myocardial infarction. Methods: COX-2 expression was evaluated by specific immunostaining in cardiomyocytes from 23 subjects who died 10–60 days after acute myocardial infarction. The relation between COX-2 myocardial expression and apoptotic rate was investigated. Cardiomyocyte apoptotic rate was defined as the number of cells co-expressing in situ end labelling of DNA fragmentation (TUNEL) and immunostaining for activated caspase-3. Results: COX-2 expression was found in cardiomyocytes at the site of infarction in nine of 23 cases (39%). It was associated with fivefold higher apoptotic rates (median 17.9% (interquartile range 11.0–25.4%) v 3.7% (0.6–12.8%); p  =  0.016), and apoptotic rate increased progressively from mild to intense COX-2 staining (p for trend 0.009). COX-2 expression co-localised with TUNEL nuclear staining in myocytes, and there was a high concordance between COX-2 and hypoxia induced factor 1-α staining (78%, p  =  0.021) and between COX-2 and bax (83%, p  =  0.014). Subjects showing myocardial COX-2 expression were more likely to have enlarged hearts (p  =  0.050), and intense COX-2 staining was strictly associated with symptomatic heart failure (p  =  0.035). Conclusions: COX-2 is expressed in cardiomyocytes in nearly 40% of cases at the site of recent acute myocardial infarction, even late after the index event. Its expression was associated with extremely high apoptotic rates. These findings suggest a potential cause–effect link between COX-2 expression and enhanced myocardial apoptosis in ischaemic cardiomyopathy.